Progress in dairy science - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Progress in dairy science edited by C J C Phillips 1995 416pp price UKL60.00 ISBN 0 85198 9748